2015
DOI: 10.1130/g37000.1
|View full text |Cite
|
Sign up to set email alerts
|

Lycopsid forests in the early Late Devonian paleoequatorial zone of Svalbard

Abstract: The Middle to early Late Devonian transition from diminutive plants to the first forests is a key episode in terrestrialization. The two major plant groups currently recognized in such "transitional forests" are pseudosporochnaleans (small to medium trees showing some morphological similarity to living tree ferns and palms) and archaeopteridaleans (trees with woody trunks and leafy branches probably related to living conifers). Here we report a new type of "transitional" in-situ Devonian forest based on lycops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 14 publications
0
81
0
Order By: Relevance
“…This assessment is based on shared synapomorphies including bipolar growth from a shoot like "rhizomorph" structure and secondary woody tissue [48]. Arborescent lycopsids are known from the Frasnian [122,123] (382.7-372.2 Ma), although the rhizomorph root structure could not be identified in these early fossils. However, discovery of a putatively homosporous arborescent lycopsid (the Isoetales are heterosporous) suggests that arborescence could be a convergent phenotype within the lycopods [124].…”
Section: Calibration Pointsmentioning
confidence: 99%
“…This assessment is based on shared synapomorphies including bipolar growth from a shoot like "rhizomorph" structure and secondary woody tissue [48]. Arborescent lycopsids are known from the Frasnian [122,123] (382.7-372.2 Ma), although the rhizomorph root structure could not be identified in these early fossils. However, discovery of a putatively homosporous arborescent lycopsid (the Isoetales are heterosporous) suggests that arborescence could be a convergent phenotype within the lycopods [124].…”
Section: Calibration Pointsmentioning
confidence: 99%
“…As regards the Spitsbergen form Asterolepis scabra, it is found in the Fiskløfta Member of the Tordalen Formation in the Mimer Valley. There has been some debate on the age of these deposits (see Berry and Marshall, 2015;Piepjohn and Dallmann, 2014) but Newman et al (2019) have shown without doubt that the Fiskeløfta Member is stratigraphically higher than the Rousay Flagstone Formation, notwithstanding the morphological differences between the two species pointed out above. The other species of Asterolepis can all be FIGURE 17.…”
Section: Discussionmentioning
confidence: 99%
“…Ellesmerian contraction, which is believed to have initiated after the deposition of the Fiskekløfta Formation in the late-latest Givetian (i.e., latest Middle Devonian; Berry and Marshall, 2015) and terminated prior to the deposition of middle-late Famenian-Mississippian (Scheibner et al, 2012; 1080 https://doi.org/10.5194/se-2019-200 Preprint. Discussion started: 13 January 2020 c Author(s) 2020.…”
Section: New Paleontological and Palynological Data Cast New Light Onmentioning
confidence: 99%